An easy-to-use AIHF-nomogram to predict advanced liver fibrosis in patients with autoimmune hepatitis - Zhang, Zhiyi; Wang, Jian; Wang, Huali; Qiu, Yuanwang; Zhu, Li; Liu, Jiacheng; Chen, Yun; Li, Yiguang; Liu, Yilin; Chen, Yuxin; Yin, Shengxia; Tong, Xin; et al. (Frontiers in Immunology, 2023)
Background The evaluation of liver fibrosis is essential in the management of patients with autoimmune hepatitis (AIH). We aimed to establish and validate an easy-to-use nomogram to identify AIH patients with advanced liver fibrosis. Methods AIH patients who underwent liver biopsy were included and randomly divided into a training set and a validation set. The least absolute shrinkage and selection operator (LASSO) regression was used to select independent predictors of advanced liver fibrosis from the training set, which were utilized to establish a nomogram. The performance of the nomogram was evaluated using receiver characteristic curve (ROC), calibration curve, and decision curve analysis (DCA). Results The median age of 235 patients with AIH was 54 years old, with 83.0% of them being female. Six independent factors associated with advanced fibrosis, including sex, age, red cell distribution width, platelets, alkaline phosphatase, and prothrombin time, were combined to construct a predictive AIH fibrosis (AIHF)-nomogram. The AIHF-nomogram showed good agreement with real observations in the training and validation sets, according to the calibration curve. The AIHF-nomogram performed significantly better than the fibrosis-4 and aminotransferase-to-platelet ratio scores in the training and validation sets, with the area under the ROCs for predicting advanced fibrosis of 0.804 in the training set and 0.781 in the validation set. DCA indicated that the AIHI-nomogram was clinically useful. The nomogram will be available at http://ndth-zzy.shinyapps.io/AIHF-nomogram/ as a web-based calculator. Conclusions The novel easy-to-use web-based AIHF-nomogram model provided an insightful and applicable tool to identify AIH patients with advanced liver fibrosis.